Circadian rhythm pattern of symptom onset in patients with ST-segment elevation myocardial infarction in the Chinese population - Guo, Yibo; Cui, Lina; Li, Lulu; Wang, Zhuozhong; Fang, Chao; Yu, Bo (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe peak incidence of cardiovascular diseases (CVD) usually occurs in the morning. This study aimed to investigate the exact distribution pattern of peak incidence of ST-segment elevation myocardial infarction (STEMI) in the Chinese population, and to explore whether it is associated with the prognosis.MethodsThis study included 7,805 patients with STEMI from the multicenter, prospective AMI cohort in China, for whom had a definite time of symptom onset. In the overall population and the predefined subgroup populations, the circadian rhythms of STEMI onset were statistically analyzed. Then patients were divided into four groups based on the time of onset (6 h interval) to assess the association of symptom onset time and major adverse cardiovascular and cerebrovascular events (MACCE) after discharge.ResultsThe onset of STEMI had a bimodal distribution: a well-defined primary peak at 8:38 AM [95% confidence interval (CI): 7:49 to 9:28 AM], and a less well-defined secondary peak at 12:55 PM (95% CI: 7:39 AM to 18:10 PM) (bimodal: P < 0.001). A similar bimodal circadian rhythm pattern was observed in subgroups of patients with STEMI defined with respect to day of the week, age, sex, and coronary risk factors. Notedly, the two peaks on Sunday were significantly later than other days, and the secondary peaks became clear and concentrated. In addition, no significant difference was found in MACCE among the four groups (P = 0.905).ConclusionsIn the Chinese population, the onset of STEMI exhibited a bimodal circadian rhythm pattern, with a clear primary peak and a less clear secondary peak. One-year clinical outcomes were unrelated to the timing of STEMI onset.